Investigation of warfarin overdose and related factors in the emergency department - Çınaroğlu, Osman Sezer; Şengül, Melih; Çınaroğlu, Deniz; Coşkun, Semih Musa; Bora, Ejder Saylav (The European Research Journal, 2024)
Objectives: This study aims to analyze the clinical features, symptoms, laboratory findings, and treatment approaches of patients presenting to the emergency department with elevated INR due to warfarin overdose. Methods: The study was conducted retrospectively from August 1, 2023, to June 1, 2024, in the emergency department of a tertiary hospital in a city with a population of 5 million. Patients aged 18 and over with an INR value of 3.5 or above were included. Data were obtained from electronic health records and patient files. Statistical analyses were performed using IBM SPSS Statistics. Results: A total of 121 patients were included in the study. The mean age was 71.85±12.28 years, with 53.7% female and 46.3% male. The most common diagnoses were atrial fibrillation (33.1%) and valve replacement (31.4%). The main reasons for emergency admission included general condition disorder (22.3%) and abdominal pain (16.5%). The bleeding rate was 47.9%, with the gastrointestinal system being the most common bleeding site (49.2%). The mean INR value was 9.27±5.45. Vitamin K was administered to 47.1% of patients and fresh frozen plasma to 28.1%. The discharge rate was 38.8%, and the mortality rate was 2.5%. Conclusions: Patients presenting to the emergency department with warfarin overdose are at significant risk of severe bleeding, requiring careful management. Close monitoring and accurate dose adjustments are essential, especially in elderly and comorbid patients. Antidotes such as vitamin K, fresh frozen plasma, and prothrombin complex are effective in managing bleeding complications. Future studies should aim to standardize and enhance the effectiveness of these treatment protocols.